การวิเคราะห์ลูกค้าของสตาร์ เอวีนิว ไลฟ์สไตล์มอลล์ - ณภัทรามณ จึงตระกูล (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
This study aimed to analyze customers of the Star Avenue Lifestyle Mall. Questionnaires were used as the tool to collect data from 300 samples who were the customers of the Star Avenue Lifestyle Mall and those were selected by the area random sampling method. Data obtained were, then, analyzed by the descriptive statistics: frequency, percentage, and means, the inferential statistics: T-test, and the One Way ANOVA (F-test). The findings presented that most respondents were female in the age of 20-29 years old and single. They hold the bachelor’s degree as their highest level education and recently were the student. They got average monthly income at less than 15,000 Baht and resided in Chiang Mai province. According to the study on customer behavior in receiving services at the Star Avenue Lifestyle Mall, the results revealed that most of them took restaurant and beverage services. They usually visited the Star Avenue Lifestyle Mall in the evening (18.01-24.00 hrs) of the convenient day with uncertain frequency and with the average amount of expenses at 500-2,000 Baht. Most of them made the decision to visit the Star Avenue Lifestyle Mall by themselves with the reason of its convenient location. The majority perceived information of the Star Avenue Lifestyle Mall from the recommendations of acquaintances and would return to the studied mall in the future. According to the study on four marketing mix factors that might affect customer decision towards receiving services at the Star Avenue Lifestyle Mall, the results suggested that all studied factors namely place, product, price, and promotion, respectively affected the customer decision at high level. The top ten sub-factors, as listed in descending order, which affected the customer purchasing decision were the convenient location near community area, bus station, school, hospital, and tourist attractions, the uniqueness-beauty-and modernity of the studied mall, the proper zoning arrangement which was convenient and easy to purchase products or services, as well as the full facilities such as parking space, toilets, resting area, bins, and ATM services as equally found in all zones, the large, clear, clean, and beautiful area, the diversity of shops, the availability of trendy products and services, the attractive promotions (discount/redeem/reward/premium), the quality of products or services, the safety to walk around in the studied mall, and the large size of billboards to promote the studied mall at many visible places. In addition, the results presented that in an overview, the respondents in different ranges of age and monthly income had different concern on place factor, especially on the sub-factor of convenient location near community area, bus station, school, hospital, and tourist attractions, at 0.05 level of statistical significance. In the meanwhile, the respondents in different groups of career had different concern on price factor, especially on the sub-factor of appropriate service hours, at 0.05 level of statistical significance. Those respondents who were interested in different types of product or service had different concern on promotion factor, especially on the sub-factor of fame of the Star Avenue Lifestyle Mall, at .05 level of statistical significance.